Regional Commissions to Monitor Confinement Institutions: A Proposal - Landever, Arthur R. (1973)
On any given day, there are more than one million persons in- voluntarily confined within government institutions. Those in custody whether committed to mental institutions, jails, juvenile facilities, or prisons, are the invisible Americans. Until recently, most of us on the outside were not particularly concerned about their lot. To the extent that we knew of their existence, we were relieved that they were out of our immediate neighborhoods and that we were protected from them. Increasingly, however, newspaper headlines or television screens have begun to show glimpses of these inmates as they riot; widespread abuses are exposed, and authorities across the ideological spectrum bemoan the non-treatment, inhumanity, or schools for crime found within the walls of their closed societies